Points of interest in the city of Barcelos in Portugal through augmented reality - Miguel Pereira; João Carlos Silva; Marisa Pinheiro; Sandro Carvalho; Gilberto Santos (Internet of Things and Cyber-Physical Systems)
Barcelos is a historic city in Portugal with many tourist attractions, attracting more and more visitors who come to the city with the aim of exploring it. The main objective of this article is to boost tourism in the city of Barcelos, specifically highlighting tourist, historical and leisure spots, based on the development of a mobile application using augmented reality technologies and geolocation. This application intends to allow the users to know historical points of interest in Barcelos, as well as interact with a certain point. The results of this investigation were evaluated by testing the application by end users, with the aim of identifying whether the application meets their needs, in particular the promotion of tourist and historical points.